Jewish interpretation of the Bible : ancient and contemporary - Zetterholm, Karin (Fortress Press, 2012)
"Although Jewish tradition gives tremendous importance to the Hebrew Bible, from the beginning Jewish interpretation of those scriptures has been practiced with remarkable freedom. Karin Hedner Zetterholm introduces the legal, theological, and historical presuppositions that shaped the dominant stream of rabbinic interpretation, including Mishnah, Talmud, and Midrashim, discussing examples of different interpretive methods, and explores the contours of Jewish biblical interpretation evident in the New Testament and the legacy of ancient traditions in the way different Jewish movements read the Bible today. Students of the history of biblical interpretation and of Judaism will find this an important and engaging resource."--Publisher description